Increased protein sorption in poly(acrylic acid)-containing films through incorporation of comb-like polymers and film adsorption at low pH and high ionic strength - Ma, Yiding (Langmuir : the ACS journal of surfaces and colloids, 2013)
In principle, incorporation of comb-like block copolymers in multilayer polyelectrolyte films can both increase film thickness relative to coatings containing linear polymers and provide more swollen films for increased sorption of proteins. In the absence of added salt, alternating adsorption of 5 bilayers of protonated poly(allylamine) (PAH) and comb-like poly(2-hydroxyethyl methacrylate)-graft-poly(acrylic acid) (PHEMA-g-PAA) leads to ∼2-fold thicker coatings than adsorption of PAH and linear PAA, and the difference in the thicknesses of the two coatings increases with the number of bilayers. Moreover, the (PAH/PHEMA-g-PAA)n films sorb 2- to 4-fold more protein than corresponding films prepared with linear PAA, and coatings deposited at pH 3.0 sorb more protein than coatings adsorbed at pH 5.0, 7.0, or 9.0. In fact changes in deposition pH and addition of 0.5 M NaCl to polyelectrolyte adsorption solutions alter protein sorption more dramatically than variations in the constituent polymer architecture. When deposited from 0.5 M NaCl at pH 3.0, both (PAH/PHEMA-g-PAA)5 and (PAH/PAA)5 films increase in thickness more than 400% upon adsorption of lysozyme. These films contain a high concentration of free -COOH groups, and subsequent deprotonation of these groups at neutral pH likely contributes to increased protein binding. Lysozyme sorption stabilizes these films, as without lysozyme films deposited at pH 3.0 from 0.5 M NaCl desorb at neutral pH. Films deposited at pH 9.0 from 0.5 M NaCl are more stable and also bind large amounts of lysozyme. The high binding capacities of these films make them attractive for potential applications in protein isolation or immobilization of enzymes